(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2020)
The presence of different groups of freshwater fish are the result of speciation events in the Ecuadorian coast, this due to geomorphological factors and climatic variations. The Trichomycteridae family is a representative of this evolutionary process, however, there are limited studies. In this work, the representatives of this family in two communes in the Chongón – Colonche mountain were described and identified. The identified species were; 30 individuals for Trichomycterus taenia for Dos Mangas and 34 individuals such as Trichomycterus cf. Taenia for Loma Alta, through linear regressions, it was determined that the relationships between the analyzed variables evidenced a linear trend with a correlation coefficient greater than R = 0.89. Slope values (b) demonstrated negative allometric growth (b <1) in all the regressions. A morphometric variation analysis was performed where a decrease in head length and width was observed in specimens from the Loma Alta commune, so it is presumed that the specimens collected in Loma Alta may be a possible morphotype of Trichomycterus taenia.